The Expanding Global Income Gap: How Reliable is the Evidence ? - Radetzki, Marian
Employing exchange rate determined per capita GTPs, the article demostrates a very sharp increase in global income inequality. In 1960, the gar between country groups representing the poorest and richest population deciles equalled 40, and there were widespread fears that the larde income gap was a threat to sustainable global economic expansion. By 1995, the poor group per capita incomes had declined by almost 50 per cent in real terms, and the gap had widened 140. These finding are in sharp contrast to the results from the increasingly fashionable assessments employing PPP-adjusted incomes figures. The latter show a positive incomes trend for the poorest decile, and an insignificant increase in the rich/poor incomes gapágina It is well known that exchange rate determined internacional GDP comparisons exaggerate the income gaps between rich and poor nations. But it is far from obvious that PPP adjustments yield results that are superior to those obtained with the help of exchenge rates, when the relative gaps are compared at different points in time, or when per capita incomes are tracked over logn time periods in individual countries or countries groups. Our dramatic results, therefore, represent a very important second opinion on what has happened to global incomes distribution